The Common Core State Standards' Quantitative Text Complexity Trajectory: Figuring Out How Much Complexity Is Enough. (March 2013) - Williamson, Gary L.; Fitzgerald, Jill; Stenner, A. Jackson
The Common Core State Standards (CCSS) set a controversial aspirational, quantitative trajectory for text complexity exposure for readers throughout the grades, aiming for all high school graduates to be able to independently read complex college and workplace texts. However, the trajectory standard is presented without reference to how the grade-by-grade complexity ranges were determined or rationalized, and little guidance is provided for educators to know how to apply the flexible quantitative text exposure standard in their local contexts. We extend and elaborate the CCSS presentation and discussion, proposing that decisions about shifting quantitative text complexity levels in schools requires more than implementation of a single, static standard. A rigorous two-part analytical strategy for decision making surrounding the quantitative trajectory standard is proposed, a strategy that can be used by state policy makers, district officials, and educators in general. First, borrowing methods from student growth modeling, we illustrate an analytical method for creation of multiple trajectories that can lead to the CCSS end-of-high-school target for text complexity exposure, resulting in trajectories that place greater burden for shifting text complexity levels on students in different grades. Second, we submit that knowledge of the multiple possibilities, in conjunction with a set of guiding principles for decision making, can support educators and policy makers in critiquing and using the CCSS quantitative standard for text complexity exposure to establish particular expectations for quantitative text complexity exposure for particular students in situ.